2020
DOI: 10.4300/jgme-d-19-00793.1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Flourishing Among Internal Medicine and Psychiatry Residents

Abstract: Background Many residents experience burnout, prompting national attention to well-being; however, well-being is not merely the absence of burnout. A recently developed measure of flourishing may provide insight on this important topic. Objective We investigated flourishing in a sample of medical residents. Methods Internal medicine residents and psychiatry residents at 2 residency programs responded to a cross-sectional online survey (December 2017–February 2018), which focused on the Flourish Index (FI) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
0
15
1
Order By: Relevance
“…Incorporating positive psychological measurements and approaches into healthcare trainee programs is a common mandate and point of emphasis [ 85 , 112 , 113 , 114 , 115 ], and our findings point to socio-demographic factors and behavioral associations that can help identify and refine impactful and feasible programming to bolster healthcare trainee flourishing. Our findings indicate that facilitating the behaviors associated with flourishing is especially critical among primary caregivers to improve well-being and reduce loneliness and stress.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Incorporating positive psychological measurements and approaches into healthcare trainee programs is a common mandate and point of emphasis [ 85 , 112 , 113 , 114 , 115 ], and our findings point to socio-demographic factors and behavioral associations that can help identify and refine impactful and feasible programming to bolster healthcare trainee flourishing. Our findings indicate that facilitating the behaviors associated with flourishing is especially critical among primary caregivers to improve well-being and reduce loneliness and stress.…”
Section: Discussionmentioning
confidence: 87%
“…These data were collected from the subset of trainees who chose to participate in a larger study that evaluated a mindfulness intervention, and it is possible that self-selection biases influenced our dataset such that the symptoms, well-being, and physiology of our sample is not representative of the larger population. Here, we used the MHC-SF to quantify flourishing, but other flourishing measures have been used in the context of physician residents [ 112 ]. Interestingly, to our knowledge, the only other study to examine flourishing using an alternative measure found results that are discrepant with those found here and with the other studies that used the MHC-SF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the limited literature on mental health professionals’ positive wellbeing, only one cross-sectional study measured psychological flourishing among mental health professionals (i.e., psychiatrists residing in a hospital setting), and its findings showed that high quality of life, high work-life balance satisfaction, and low emotional exhaustion were significantly associated with psychological flourishing (Kelly-Hedrick et al, 2020 ). However, organizational factors were not included and so the degree to which distal factors in the workplace are related to mental health professionals’ psychological flourishing remains unknown.…”
Section: Mental Health Professionals’ Wellbeingmentioning
confidence: 99%
“…To our best knowledge, three studies thus far have been conducted to test the relationship between emotional exhaustion and psychological flourishing. Although these studies were limited due to their cross-sectional design, they consistently showed that those employees who were more emotionally exhausted scored lower on psychological flourishing in samples of teachers, internists, and psychiatrists residing in hospitals, as well as gynecologic cancer specialists (Freire et al, 2020 ; Kelly-Hedrick et al, 2020 ; Vetter et al, 2018 ). The various stressors, including negative emotional experiences, encountered by emotionally exhausted individuals leave them with impaired psychosocial functioning and poorer work performance (Cropanzano et al, 2003 ; Tuithof et al, 2017 ); therefore, they retain insufficient capacity for psychological flourishing.…”
Section: Mediation Effect Of Emotional Exhaustionmentioning
confidence: 99%